High Intensity Interval Training as a Therapeutic Exercise Strategy for Patients with Chronic Kidney Disease - Carlos Alberto Romero Cuestas; Brian Johan Bustos Viviescas; Carlos Enrique García Yerena (Revista Finlay, 2025)
Chronic kidney disease requires therapeutic treatment that develops and combines lifestyle changes, monitoring, management of comorbidities, and physical exercise. From the above, it follows that high-intensity interval training has become an important and effective strategy for improving cardiorespiratory fitness, training tolerance, and lipid profile control in patients with chronic kidney disease. It is important to note that high-intensity interval training can decrease renal blood flow due to muscle redistribution, and proper monitoring and management contribute to risk reduction. Thus, training has become an option for patients because it directly improves quality of life.